Trend and research focus on Problem-Based Learning and learning outcome in the world: A bibliometric analysis - Agus Fatkhurohman Handoyo; Ade Sobandi; Widhi Ariyo Bimo (Himpunan Pengembang Kurikulum Indonesia, 2024)
A problem-based learning approach is a learning approach that is student-centered, allowing them to confront real-world problems, encouraging critical thinking, collaboration and problem solving. This research aims to investigate several key aspects related to PBL and learning outcomes at a global level and generate in-depth insights into research trends and focuses related to problem-based learning (PBL) approaches and learning outcomes. through bibliometric analysis. From 1132 Scopus database articles, after going through the selection process there were 742 articles. It was found that interest and research focus on this topic has increased significantly in recent years, reflecting the importance of PBL in developing students' critical and collaborative skills. The importance of developing valid and reliable educational measurement tools to measure learning outcomes. The importance of international collaboration in enriching understanding of PBL and learning outcomes. Human factors, such as student characteristics, were found to be important in designing a PBL curriculum that is responsive to student needs. These findings provide guidance for future research directions, highlighting the innovative potential in PBL development. In conclusion, these results and discussion provide a strong foundation for the development of education oriented towards effective learning outcomes in the modern era. Abstrak Pendekatan pembelajaran berbasis masalah adalah pendekatan pembelajaran yang berpusat pada peserta didik, memungkinkan mereka menghadapi masalah dunia nyata, mendorong pemikiran kritis, kolaborasi, dan pemecahan masalah. Penelitian ini bertujuan untuk menyelidiki beberapa aspek kunci terkait dengan PBL dan hasil pembelajaran di tingkat global dan menghasilkan wawasan mendalam tentang tren dan fokus penelitian terkait pendekatan pembelajaran berbasis masalah (PBL) dan hasil pembelajaran. melalui analisis bibliometrik. dari sebanyak 1132 artikel database scopus, setelah melalui proses seleksi menjadi 742 artikel. Ditemukan bahwa minat dan fokus penelitian terhadap topik ini meningkat secara signifikan dalam beberapa tahun terakhir, mencerminkan pentingnya PBL dalam mengembangkan keterampilan kritis dan kolaboratif peserta didik. Pentingnya pengembangan alat pengukuran pendidikan yang valid dan reliabel untuk mengukur hasil pembelajaran. Pentingnya kerja sama internasional dalam memperkaya pemahaman tentang PBL dan hasil pembelajaran. Faktor-faktor manusia, seperti karakteristik peserta didik ditemukan penting dalam merancang kurikulum PBL yang responsif terhadap kebutuhan peserta didik. Temuan ini memberikan panduan arah penelitian mendatang, menyoroti potensi inovatif dalam pengembangan PBL. Kesimpulannya, hasil dan pembahasan ini memberikan landasan yang kuat untuk pengembangan pendidikan yang berorientasi pada hasil pembelajaran yang efektif di era modern. Kata Kunci: bibliometrik; hasil belajar; pembelajaran berbasis masalah